O UNIVERSO MÁGICO DA GEOMETRIA: UMA PROPOSTA DE SEQUÊNCIA DIDÁTICA PARA A EDUCAÇÃO INFANTIL - Spode, Graziela Espindola Mezzomo (2023)
This project is linked to the Professional Master's Course of the Graduate Program in Teaching Science and Mathematics at the Franciscan University and aims to identify the potential that a didactic sequence, built from the plot "The Magical Universe of Geometry", has for the teaching of Geometry in Early Childhood Education. The studies were carried out through bibliographic research, development and application of a didactic sequence in an Early Childhood Education class at a Municipal School in Santa Maria, RS. The theoretical bases were permeated by authors who bring studies about the teaching of Mathematics in Early Childhood Education, about the teaching of Geometry and the importance of playfulness. The didactic sequence was created from a plot called “The Magical Universe of Geometry”, based on the importance of teaching Mathematics in Early Childhood Education and the need for tools and theoretical contributions for this Teaching. Our data collection was carried out through the application of the sequence, where the main moments were recorded through audio and images. Data were analysed based on the assumptions of explanatory and descriptive research. Considering our objectives, the relevance of our research became clear, showing as main results the interest aroused in children by the topic at hand, the provocations created in relation to the environment in which they live, when they began to observe it and visualize its forms and previously unnoticed contexts. The work proved to be efficient when adding the teaching practice as a tool and a resource for the teaching of geometry, being able to awaken in the teacher and evidently in the student a new way of seeing this area of mathematics.